2021
DOI: 10.47895/amp.v55i8.2125
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Analysis and Antibacterial Activity of Purple Leaf Extract [Graptophyllum pictum (L.) Griff] Against Streptococcus mutans

Abstract: Background. Streptococcus mutans is the leading cause of dental caries. One of many medicinal plants, purple leaf [Graptophyllum pictum (L.) Griff], which contains flavonoids, alkaloids, tannins, steroids, and saponins, is a potential antibacterial agent. Objective. This study aimed to determine the antibacterial activity of purple leaf extract (Graptophyllum pictum L. Griff) against Streptococcus mutans. Methods. Streptococcus mutans were suspended in several Graptophyllum pictum (L.) Griff extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 9 publications
0
11
0
1
Order By: Relevance
“…Jiratanakittiwat et al 41 showed that an ethanol solvent is the best diluent for getting the best extraction results; a higher ethanol content and a longer time extraction period will give rise to a higher oxyresveratrol content. 42 In this research, an ethanol solvent was used for ethanol extraction using mobe leaves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jiratanakittiwat et al 41 showed that an ethanol solvent is the best diluent for getting the best extraction results; a higher ethanol content and a longer time extraction period will give rise to a higher oxyresveratrol content. 42 In this research, an ethanol solvent was used for ethanol extraction using mobe leaves.…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoid compounds work against bacteria in a number of ways, e.g., preventing the production of nucleic acids, the function of cytoplasmic membranes, preventing bacteria from using oxygen for energy metabolism, and preventing the synthesis of cell membranes by forming intricate compounds with extracellular proteins. 42,[45][46][47][48] Joycharat et al 49 studied the antibacterial effect of flavonoids on S. mutans ATCC 25175 bacteria using an Albizia myriophylla wood ethanol extract. The results showed that lupinifoline (from the flavonoid group) had an antibacterial effect that was almost comparable to 0.5 µg/ml chlorhexidine.…”
Section: Discussionmentioning
confidence: 99%
“…Kulit dan daun berlendir berbau kurang enak (Kariman, 2014). Senyawa metabolit sekunder yang terkandung di dalam daun ungu meliputi steroid, alkaloid, flavonoid, saponin dan tanin sehingga memiliki potensi sebagai antibakteri (Juniarti et al, 2021). Secara empiris daun ungu telah digunakan masyarakat Bumi Patowonua sebagai antibakteri, mengatasi wasir dan sembelit, dengan cara dimasak daun ungu dengan sedikit air, setelah mendidih disaring.…”
Section: Daun Ungu ( Graptophylum Pictum )unclassified
“…Phytochemical analysis of purple leaves revealed the presence of flavonoids, steroids, glycosides, tannins, saponins, chlorophyll, nontoxic alkaloids, and anthocyanins (Makkiyah et al, 2021). Research on the antibacterial activity of purple leaves extract against L. acidophilus has been carried out using the liquid dilution method to obtain a Minimum Inhibitory Concentration (MIC) of 6.25% (Juniarti et al, 2021). However, determining MIC by dilution is difficult for dark concentrated extracts (Sari et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, determining MIC by dilution is difficult for dark concentrated extracts (Sari et al, 2015). Purple leaves extract has a deep purple-black color due to the high content of flavonoids (Juniarti et al, 2021). Therefore, research is needed to determine MIC with other methods.…”
Section: Introductionmentioning
confidence: 99%